A combination of context-fuzzy clustering method and learning with forgetting algorithm in a neural network model to generating fuzzy rules - Cuong, Bui Cong; Phuc, Le Quang; Binh, Nguyen Thi An (Journal of Computer Science and Cybernetics, 2012)
See full text.